GAYA HIDUP REMAJA PENGGUNA SMARTPHONE DI KOTA MALANG - Muhammad Tony Irwanto (Universitas muhammadiyah malang, 2016)
The purpose of this study had identify and analyze the youth lifestyle Smartphone users in Malang. The usefulness of this research can be used as the basis for the company's consideration in developing Smartphone products produced and tailored to the consumer'lifestyle. Population in this study is that consumers Smartphone users in Malang, with characteristics that respondents who have entered in the category of age and adolescents, using judgmental sampling techniques can then be determined as many as 100 sample. Data analysis techniques used in this research is the analysis of the cluster. From the results of research and discussion, it can be concluded that the cluster I have a characteristic that is the willingness of respondents to support the work ruitn performed, work or routine activities are carried out, the development of information media, the activities undertaken by a person as a source of income, neighborhood closest to a person , always had a desire to buy the latest products, more priority to the purchase of goods after the wants rather than needs, support penampilandan add relationships / peer. Cluster III has the characteristic that the respondent wishes to keep up with technology, where it makes the respondent is always working to get information lengkao by utilizing technological developments.